VO2max, ventilatory and anaerobic thresholds in rhythmic gymnasts and young female dancers - Baldari, C.; Guidetti, L. (The Journal of Sports Medicine and Physical Fitness, 2001)
This study examines the fitness level of a rhythmic gymnasts group and a young female classical dancers group. METHODS: Aerobic power (VO2max), individual ventilatory (IVT) and anaerobic thresholds (IAT) were assessed in 12 elite rhythmic gymnasts, eight elite ballet dancers and 12 sedentary female subjects in the same age range (13-16 yrs). The VO2max, IVT and IAT were assessed during a continuous incremental running treadmill test. RESULTS: At IVT and IAT the VO2max expressed in ml.kg-l.min-l was significantly different between the three groups of subjects. The highest values were found in gymnasts (30.8+/-2.6 for IVT and 43.8+/-3.5 for IAT) followed by the values of dancers (21.7+/-2.8 for IVT and 30.5+/-3.1 for IAT) and controls (15.6+/-2.0 for IVT and 20.6+/-1.7 for IAT). When the VO2max was expressed in percent of VO2max, the values at IAT were significantly different between all groups (gymnasts: 84.9+/-0.7; dancers: 64.0+/-4.1; controls: 59.7+/-2.4) while at IVT no difference was found between dancers and controls (45.6+/-4.1 and 45.2+/-16, respectively). At maximal effort VO2 was significantly higher both in gymnasts and dancers (51.7+/-4.4 and 47.5+/-3.0 ml.kg-l.min-l, respectively), than in controls (34.5+/-2.5 ml.kg-l.min-l). CONCLUSIONS: Although VO2max was similar between gymnasts and dancers, VO2 values at NT and IAT were able to discriminate the higher level of fitness in gymnasts with respect to dancers.